BIOLOGICAL EFFECTIVENESS OF APPLICATION OF BIFSTAR 10% EM.K PREPARATION IN GROWING PEAR SEEDLINGS (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
This article presents an analysis of the results of experiments conducted to determine the biological effectiveness of chemical preparations against root pests of pear seedlings - cockchafer (Scarabaeidae) beetles. Bifstar 10% em.k (bifenthrin) was selected as the chemical preparation, which was used at a consumption rate of 1 l/ha.